53rd AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics and Materials Conference<BR&amp;gt;20th AIAA/ASME/AHS Adapti 2012
DOI: 10.2514/6.2012-1735
|View full text |Cite
|
Sign up to set email alerts
|

Inverse load calculation of wind turbine support structures - a numerical verification using the comprehensive simulation code FAST

Abstract: Physically measuring the dynamic responses of wind turbine support structures enables the calculation of the applied loads using an inverse procedure. In this process, inverse means deriving the inputs/forces from the outputs/responses. This paper presents results of a numerical verification of such an inverse load calculation. For this verification, the comprehensive simulation code FAST is used. FAST accounts for the coupled dynamics of wind inflow, aerodynamics, elasticity and turbine controls. Simulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…A third load case with a mean wind speed of 18 m s −1 , at a rotor speed of 12 rpm, confirms the observed characteristics. A description of this load case as well as more information about how the control system influences the inverse calculation are provided in Pahn et al …”
Section: Results From Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A third load case with a mean wind speed of 18 m s −1 , at a rotor speed of 12 rpm, confirms the observed characteristics. A description of this load case as well as more information about how the control system influences the inverse calculation are provided in Pahn et al …”
Section: Results From Simulationsmentioning
confidence: 99%
“…A third load case with a mean wind speed of 18 m s À1 , at a rotor speed of 12 rpm, confirms the observed characteristics. A description of this load case as well as more information about how the control system influences the inverse calculation are provided in Pahn et al 25 The summary of results for the land-based simulations makes clear that the inverse calculation approach is able to generate good estimates for the rotor thrust force. Amplifications are observed that are caused by the 3-P excitation and the eigenfrequencies of the rotor blades.…”
Section: **mentioning
confidence: 99%
“…FOWTs operate over a wide range of wind speeds (typically between 5 and 40 knots) and their operating principle is that the blade speed is essentially constant. In practice, as shown by Pahn et al (2012) in real cases, the tower of a wind turbine is subjected to a thrust force composed of an almost constant term and a periodic force 𝐹 (𝑡) = 𝐴 0 + 𝐴 cos 𝜔𝑡 with 𝜔 = 2𝜋 𝑓 where 𝑓 is the force frequency, which depends mainly on the wind speed variations, the rotation speed and the number of blades of the FOWT. In the various cases considered in this work, most of the dynamic components are below 1 Hz with a maximum amplitude of about 10 kN.…”
Section: Introductionmentioning
confidence: 99%